Stability of Euler's method for evaluating large deformation of shear deformable plates by dual reciprocity boundary element method - Purbolaksono J.; Aliabadi M.H. (Elsevier Ltd, 2023)
In this paper the dual reciprocity boundary element method (DRBEM) is employed to evaluate large deformations of shear deformable plates. Incremental approaches utilizing the Euler method and the total incremental method are used for treating the nonlinear problems. A simple numerical algorithm for analyzing the problems is presented. Two numerical examples of square plates with different boundary conditions subjected to transverse loadings are presented to demonstrate the accuracy of the formulation. The Euler method seems to be a more stable method for treating nonlinear problems of the shear deformable plate if the dual reciprocity method is employed to evaluate the domain integrals that appear in the formulations. 2010 Elsevier Ltd. All rights reserved.